Utilization of health-related WeChat official accounts and its influencing factors among urban occupational population in China: a path analysis - Xiao-qi WANG; He ZHU; Mei LIU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo assess the utilization of health WeChat official accounts and its related factors among urban occupational population in China. Methods Using multistage cluster sampling, we recruited 7 699 employees aged 18 - 60 years working in enterprises or institutions in 6 provinces across China and conducted an online survey during October - December, 2018. A self-designed questionnaire was used to collect information on the utilization of health WeChat official accounts; multivariate linear regression and path analysis were adopted to explore major factors affecting the utilization.ResultsOf the 6 821 employees with valid responses, 5 688 (83.39%) reported the utilization of health WeChat official accounts. The results of path analysis indicated that behavioral intention, eHealth literacy and perceived susceptibility affected the frequency of health WeChat official account use directly, with direct effect value of 0.073, 0.090, and 0.088; while effort expectancy, hedonic motivation and social influence indirectly affected the frequency through behavioral intention with the path coefficients of 0.450, 0.447, and 0.447, respectively. In addition, habit, perceived barriers, perceived severity, and self-reported health were directly and indirectly related to the frequency with the total effect values of 0.450, - 0.247, - 0.061, and 0.133, respectively. ConclusionHabit and effort expectancy are the most critical factors affecting the frequency of health WeChat official accounts utilization among occupational population in China. The results suggest that guidance for utilization and improvements of interfaces of health WeChat official accounts could promote health education through the utilization of health WeChat official accounts.